2012
DOI: 10.1136/fetalneonatal-2011-301090
|View full text |Cite
|
Sign up to set email alerts
|

Continuous non-invasive cardiac output measurements in the neonate by electrical velocimetry: a comparison with echocardiography

Abstract: EV is as accurate in measuring LVO as echocardiography and the variation in the agreement between EV and echocardiography among the individual subjects reflects the limitations of both techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
143
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(151 citation statements)
references
References 15 publications
(26 reference statements)
5
143
1
2
Order By: Relevance
“…Noori et al [6] conducted a validation study based on 20 term infants and 8 of them had a PDA >2 mm. He found that EC was as accurate in measuring CO as Echo, and there was no difference in bias and precision between those with or without a hsPDA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noori et al [6] conducted a validation study based on 20 term infants and 8 of them had a PDA >2 mm. He found that EC was as accurate in measuring CO as Echo, and there was no difference in bias and precision between those with or without a hsPDA.…”
Section: Discussionmentioning
confidence: 99%
“…By using transthoracic Echo, the accuracy of EC in term [6,7] and even preterm neonates [8,9,10,11] has been described. It has been studied in different clinical scenarios including surgical ligation for patent ductus arteriosus (PDA) [12], hemodynamic transition after birth [13], caffeine administration [14], and umbilical cord milking in preterm infants [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is not possible to evaluate the proportion of infants where treatment was initiated or withheld based on low blood pressure values, but it is likely that NIRS monitoring influenced treatment strategies. Non-invasive cardiac output monitoringis a relatively simple, non-invasive monitoring tool that provides continuous estimation of cardiac output and it has been evaluated against simultaneous echo measures of left ventricular output [26,27,28,29]. Future trials are warranted to assess the benefit of this additional assessment tool in preterm infants with low blood pressure.…”
Section: Has Management Changed?mentioning
confidence: 99%
“…Preliminary data show a good agreement (bias), but a wide variation (precision) between the average left ventricular output measured by echocardiography and IEC. 31 Thus, the clinical utility of IEC in the assessment of CO in neonates will hinge on the findings of ongoing studies looking at the tightness of the agreement in the direction of CO changes between echocardiography and IEC when different treatment modalities are applied in neonates to affect CO (see below).…”
Section: Introductionmentioning
confidence: 99%
“…However, it must be emphasized that, although studies on validation of IEC have been published in the pediatric patient population, 33 it is an ongoing project in the neonatal patient population with only preliminary data available at present. 31 Therefore, as long as validation is not completed and the limitations of the use of IEC to continuously monitor systemic blood flow in neonates have not been clearly identified, the method cannot be used to perform clinical research or guide treatment in neonates with cardiovascular compromise. In addition, further studies are needed to clearly establish the clinical relevance and utility of the use of NIRS in the neonatal patient population.…”
Section: Introductionmentioning
confidence: 99%